Controlled release systems based on polyacrylates and polyacrylates/clay nanocomposites of atenolol drug. (18th March 2022) - Akelah, Ahmed; Rehab, Ahmed
Abstract: Atenolol‐polyacrylate and intercalated atenolol‐polyacrylate onto montmorillonite clay was synthesized as drug delivery systems. The synthesis was carried out by free radical homo and copolymerization of acrylate drug (atenolol) monomer with different co‐monomers. The intercalation of polymeric drug systems onto montmorillonite clay was achieved through ion exchange process. The characterization of the prepared systems was investigated by different analytical techniques. The release studies of drug (atenolol) were studied over a long time in aqueous mediums at conditions nearly present in human body. Abstract : Synthesis, characterization and release study for polymeric drug and intercalated polymeric drug.